Nematocysts of the Cubozoa - Gershwin, Lisa-Ann (Zootaxa, 2006)
Nematocysts (stinging organelles) are an important part of cnidarian identification, but the cnidomes of many species remain poorly known because of identification difficulties and confusing nomenclature. Currently, the cnidomes of 20 cubozoan species are documented in whole or in part (including four undescribed species and five newly described species); 18 of these are re-examined in detail, and the cnidomes of 13 species are newly presented. Type material was used for these studies where possible. A new category of nematocyst is designated, namely ‘p-rhopaloid’, characterized by having a v-shaped notch in the undischarged shaft, as in p-mastigophores, but having a lobed discharged shaft, as in rhopaloids; this type of nematocyst is found in both the Carybdeida and Chirodropida. Measurements, shape descriptions, and photographs are presented for all cnidomes studied. Also presented are a glossary to nematocyst terminology, descriptive sections on nematocyst nomenclature and preparation, and a key to the nematocysts of theCubozoa. Special remarks sections for taxonomists and forensic specialists are given, along with a summary of phylogenetic patterns. This catalogue will be useful to taxonomists, envenomation physicians, and toxinologists, as well as anyone wishing to identify cubozoan specimens or stings.